Advancing Knowledge on Cyanobacterial Blooms in Freshwaters - Kormas, Konstantinos Ar; Vardaka, Elisabeth (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cyanobacterial blooms are a water quality problem that is widely acknowledged to have detrimental ecological and economic effects in drinking and recreational water supplies and fisheries. There is increasing evidence that cyanobacterial blooms have increased globally and are likely to expand in water resources as a result of climate change. Of most concern are cyanotoxins, along with the mechanisms that induce their release and determine their fate in the aquatic environment. These secondary metabolites pose a potential hazard to human health and agricultural and aquaculture products that are intended for animal and human consumption; therefore, strict and reliable control of cyanotoxins is crucial for assessing risk. In this direction, a deeper understanding of the mechanisms that determine cyanobacterial bloom structure and toxin production has become the target of management practices. This Special Issue, entitled "Advancing Knowledge on Cyanobacterial Blooms in Freshwaters", aims to bring together recent multi- and interdisciplinary research, from the field to the laboratory and back again, driven by working hypotheses based on any aspect of mitigating cyanobacterial blooms, from ecological theory to applied research.